2022
DOI: 10.1002/jcp.30704
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell RNA sequencing reveals the cell types heterogenicity of human discoid lateral meniscus cells

Abstract: Discoid lateral meniscus (DLM) is more prone to injury than a normally shaped meniscus. No study has compared the gene expression and cell heterogeneity between discoid and normal menisci. We aimed to identify specific cell clusters and their marker genes in discoid meniscus, thereby providing a theoretical basis for the treatment and etiology of DLM. ScRNA-seq was used in DLM and osteoarthritis lateral meniscus (OAM) cells to identify cell subsets and their gene signatures. Pseudo-time analysis and immunohist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Therefore, they proposed that the discoid meniscus is a structural, rather than a morphological, variant. Reduced number, structural abnormalities, and disorganization of collagen fibers make them more prone to tear and degenerate [2, 22, 24].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they proposed that the discoid meniscus is a structural, rather than a morphological, variant. Reduced number, structural abnormalities, and disorganization of collagen fibers make them more prone to tear and degenerate [2, 22, 24].…”
Section: Discussionmentioning
confidence: 99%
“…20,80,81 Except for the morphological and anatomical abnormalities above, the circular collagen fibers are disintegrated and disorganized, the nutrient vessels are sparse, and mucoid degeneration often occurs. These pathological characteristics changes may be the main reason DLM is prone to lesions, degeneration, postoperative retear, and poor healing 1,3,[9][10][11][12][13][14][15][16]82,83 (Grade E).…”
Section: Etiology and Pathogenesis Of Dlmmentioning
confidence: 99%
“…The specific cell clusters contributing to meniscus aberrant degeneration demonstrated a novel mechanism of meniscus degeneration. Another study showed FCs (fibrochondrocytes) populations in meniscus cells, with COL1A1 highly expressed, increased gelatinases such as MMP2, which may contribute to cartilage homeostasis in the physiological status 102–104 …”
Section: Elucidating Molecular Mechanisms Of Osteoarthritismentioning
confidence: 99%
“…Another study showed FCs (fibrochondrocytes) populations in meniscus cells, with COL1A1 highly expressed, increased gelatinases such as MMP2, which may contribute to cartilage homeostasis in the physiological status. [102][103][104] Among the meniscus zones, the red zone is rich in blood vessels.…”
Section: Synoviummentioning
confidence: 99%